Pelatihan untuk Meningkatkan Kemampuan Pencatatan Laporan Keuangan Sederhana pada Sayuraya Kediri - Nur’Aini, Ulfa; Tamimatussa’diyah, Tamimatussa’diyah; Tarisa, Tarisa; Nafkhan, Sulthon Maulana; Mukafi, Ufi; Haryati, Islamiya Nur (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Pelatihan untuk Meningkatkan Kemampuan Pencatatan Laporan Keuangan This service aims to provide a solution to the difficulties faced by Sayuraya Kediri in recording financial reports correctly. Sayuraya Kediri is a startup located in Kediri City that provides kitchen needs online through a pre-order system. The service method used is training in recording simple financial reports aimed at business owners and employees in Sayuraya Kediri. This training includes interactive sessions, case studies, and direct practice in recording financial reports. The results of this service show that the training participants were able to develop a better understanding of the importance of recording financial reports appropriately and efficiently. They also succeeded in implementing the techniques learned to record business transactions correctly, as well as increasing their confidence in managing the financial aspects of the business. This service proves that training in recording simple financial reports has great potential to help Sayuraya Kediri business owners manage their finances effectively, thereby supporting the growth and development of their business in the long term.Atina6254@gmail.com